A Psychoacoustic NofM-type Speech Coding Strategy for Cochlear Implants - Nogueira, Waldo; Büchner, Andreas; Lenarz, Tomas; Edler, Bernd (EURASIP Journal on Advances in Signal Processing, 2005)
We describe a new signal processing technique for cochlear implants using a psychoacoustic-masking model. The technique is based on the principle of a so-called "NofM" strategy. These strategies stimulate fewer channels ( ) per cycle than active electrodes (NofM; ). In "NofM" strategies such as ACE or SPEAK, only the channels with higher amplitudes are stimulated. The new strategy is based on the ACE strategy but uses a psychoacoustic-masking model in order to determine the essential components of any given audio signal. This new strategy was tested on device users in an acute study, with either 4 or 8 channels stimulated per cycle. For the first condition (4 channels), the mean improvement over the ACE strategy was . For the second condition (8 channels), no significant difference was found between the two strategies.